2002
DOI: 10.1007/s00425-001-0711-3
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium- and iron-stress-inducible gene expression in the green alga Chlamydomonas reinhardtii : evidence for H43 protein function in iron assimilation

Abstract: Early transcriptional responses of a cell wall-deficient mutant of the green alga Chlamydomonas reinhardtii to heavy-metal stress have been investigated using the method of mRNA differential display. We have identified, sequenced, and quantified the induction of a number of transcripts that are up-regulated by a brief (2-h) exposure to 25 microm cadmium chloride, including one transcript which is also highly responsive to iron (Fe) deficiency. These transcripts represent both nuclear- and chloroplast-encoded g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 39 publications
3
43
0
2
Order By: Relevance
“…The AR has been observed in bacteria (Assis et al, 2002;Sedgwick & Lindahl, 2002;Rohankhedkar et al, 2006), yeast (Boreham & Mitchel, 1991;Gajendiran & Jeevanram, 2002), algae (Chankova & Bryant, 2001;Rubinelli et al, 2002;Chankova et al, 2007), insect cells (Savina et al, 2003), mammalian cells (Wang & Cai, 2000;Tiku & Kale, 2001;Ulsh et al, 2004;Zhou et al, 2004), human cells (Schlade-Bartusiak et al, 2002;Atanasova et al, 2005;Coleman et al, 2005;Friesner et al, 2005;Lanza et al, 2005;Seo et al, 2006) and higher plants models (Rieger et al, 1993;Panda et al, 1997;Jovtchev & Stergios, 2003;Patra et al, 2003). A study of the conditions essential for the induction of an adaptive response is of critical importance to understanding the novel biological defense mechanisms against the hazardous effects of radiation.…”
Section: Hormesis and Molecular Mechanisms Of The Adaptive Responsementioning
confidence: 99%
“…The AR has been observed in bacteria (Assis et al, 2002;Sedgwick & Lindahl, 2002;Rohankhedkar et al, 2006), yeast (Boreham & Mitchel, 1991;Gajendiran & Jeevanram, 2002), algae (Chankova & Bryant, 2001;Rubinelli et al, 2002;Chankova et al, 2007), insect cells (Savina et al, 2003), mammalian cells (Wang & Cai, 2000;Tiku & Kale, 2001;Ulsh et al, 2004;Zhou et al, 2004), human cells (Schlade-Bartusiak et al, 2002;Atanasova et al, 2005;Coleman et al, 2005;Friesner et al, 2005;Lanza et al, 2005;Seo et al, 2006) and higher plants models (Rieger et al, 1993;Panda et al, 1997;Jovtchev & Stergios, 2003;Patra et al, 2003). A study of the conditions essential for the induction of an adaptive response is of critical importance to understanding the novel biological defense mechanisms against the hazardous effects of radiation.…”
Section: Hormesis and Molecular Mechanisms Of The Adaptive Responsementioning
confidence: 99%
“…The homologue corresponds to protein ID 173281, which is immediately adjacent to H43 (protein ID 129929 in version 3.0 of the genome). Rubinelli et al had previously identified the H43 gene in a screen for genes displaying differential expression under cadmium treatment (74). Nevertheless, they suggested that the gene encodes an iron assimilation component based on its increased expression in iron-deficient Chlamydomonas and its ability to stimulate the growth of a fet3 fet4 strain of Saccharomyces cerevisiae.…”
mentioning
confidence: 99%
“…This suggests that the H43/FEA1 orthologs may be widely distributed among at least chlorophyte algae. The function of H43/FEA1 is not completely understood but one possible role may be in iron assimilation (Allen et al, 2007;Rubinelli et al, 2002). Allen et al (2007) identified FEA1, FEA2, and a candidate ferrireductase (FRE1) are expressed coordinately with iron assimilation components, and it was hypothesized that the proteins may facilitate iron uptake with high affinity by concentrating iron in the vicinity of the cells (Allen et al, 2007).…”
Section: High-co 2 Signalingmentioning
confidence: 99%
“…The signal for H43/FEA1 expression might be sensed by putative proteins localized on the cell membrane, which are influenced by protein modifiers and send the signal for H43/FEA1 expression . H43/FEA1 expression is induced under excessive levels of Cd (>25 μM) or iron-deficient conditions (<1 μM) (Allen et al, 2007;Rubinelli et al, 2002). Fei et al (2009) reported two transcriptional cis-elements that are responsive to the Fe-deficient signal (FeREs) for H43/FEA1 expression, namely FeRE1 and FeRE2, which are located at -273/-259 and -106/-85 upstream from the H43/FEA1 transcriptional initiation site.…”
Section: High-co 2 Signalingmentioning
confidence: 99%
See 1 more Smart Citation